Pengaruh Motivasi Kerja dan Kepemimpinan terhadap Disiplin Kerja Pegawai pada Kantor Balai Besar Wilayah Sungai Pompengan Jeneberang di Makassar - Resi Resi; Romansyah Sahabuddin; Burhanuddin Burhanuddin; Uhud Darmawan Natsir; Ilham Wardhana Haeruddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of work motivation and leadership on employee work discipline at the Pompengan Jeneberang River Basin Office (BBWS) in Makassar. This study uses a quantitative approach with a survey method, the sample used is 80 respondents. Data collection was carried out using questionnaires, observation, interviews and documentation. The data analysis technique used is multiple linear regression analysis using statistical product and service (SPSS) 25. The results of the study indicate that work motivation has a positive and significant influence on employee work discipline at the Pompengan Jeneberang River Basin Office. Leadership also has a positive and significant influence on employee work discipline at the Pompengan Jeneberang River Basin Office. Work motivation and leadership together have a significant influence on employee productivity at the Pompengan Jeneberang River Basin Office. Thus, the implementation of an effective leadership style and strategies to increase work motivation can be a solution in improving employee discipline and performance, which in turn will improve the quality of service and work results in government agencies. This study is expected to provide insight for further research on the factors that influence work discipline in the public sector.